Pengaruh Pemberian Insentif Terhadap Karyawan di Alfamart Raya Kertasasi - Nabila, Fathma Putri; Darul Fadli, Uus Mohammad (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The study aims to determine how incentives affect employees' performance at Alfamart Kertasari. This study uses all employees of Alfamart kertasari as a sample. Five respondents in total. The data analysis at Alfamart Kertasari demonstrates the effects of incentives on employee performance by employing qualitative analysis techniques. This study demonstrates that rewards can boost employee performance at Alfamart Kertasari.